Laser microfabrication of thin films: Part one - Micheli, F.; Boyd, I.W. (Optics and laser technology, 1986)
In this paper, the first of a series of three reviewing the subject of laser microchemical processing — a potentially powerful technique for the fabrication of a variety of micro and opto-electronics devices — a general introduction to the principle of operation is given and some mainly thermal aspects of film growth are described, for example laser annealing, oxidation, nitridation and evaporation.